Chitosan–Aloe vera Combination Enhances STRO-1, DSPP, and Reparative Dentin Formation in a Rat Model of Reversible Pulpitis - Amara Syifa Tifani; Ranny Rachmawati; Yuli Nugraeni; Adam Fauzi; Rachmi Fauziah Rahayu (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Direct pulp capping (DPC) aims to preserve pulp vitality but requires agents that are both bioactive and biocompatible. Calcium hydroxide (CaOH2) is widely used, however its long-term success is limited, and it may cause adverse effects. Natural biomaterials such as chitosan and Aloe vera have shown potential, but their combined regenerative effects are still not well understood. This study was conducted to evaluate the efficacy of chitosan–Aloe vera composites in promoting stem cell activation, odontoblast differentiation, and reparative dentinogenesis in a rat model of reversible pulpitis.METHODS: Twenty-four Wistar rats with mechanically induced reversible pulpitis were divided into six groups: normal control, reversible pulpitis, CaOH2, and chitosan–Aloe vera pastes at 20%, 30%, and 40% (CA20, CA30, CA40). Pulp capping was performed following standardized pulp exposure. After 28 days, reparative dentin thickness and dentin bridge formation were assessed histologically, and STRO-1 and dentine sialophosphoprotein (DSPP) expression were analyzed immunohistochemically.RESULTS: Dentin bridge was observed in the CA40 group, presenting the thickest dentin formation (113.5±13.5 μm). STRO-1 and DSPP were significantly higher in all chitosan–Aloe vera combination groups compared with reversible pulpitis group (p<0.01), with DSPP in CA30 and CA40 also higher than CaOH2 group. Both biomarkers demonstrated a positive correlation, and reparative dentin thickness showed a strong positive correlation with DSPP level (r=0.786, p<0.001).CONCLUSION: Chitosan–Aloe vera combination showed encouraging biological activity in this 28-day preclinical model of reversible pulpitis. Although higher concentrations enhanced stem cell activation, odontoblast differentiation, and reparative dentin formation, these results should be interpreted cautiously due to the small sample size and study design limitations.KEYWORDS: pulp capping, STRO-1, DSPP, dentin bridge, CaOH2, natural biomaterial, endodontics